2018
DOI: 10.1371/journal.pone.0206096
|View full text |Cite
|
Sign up to set email alerts
|

Identifying top 10 primary care research priorities from international stakeholders using a modified Delphi method

Abstract: BackgroundHigh quality primary care is fundamental to achieving health for all. Research priority setting is a key facilitator of improving how research activity responds to concrete needs. There has never before been an attempt to identify international primary care research priorities, in order to guide resource allocation and to enhance global primary care. This study aimed to identify a list of top 10 primary care research priorities, as identified by members of the public, health professionals working in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
0
29
0
4
Order By: Relevance
“…[4][5][6][7][8][9][10] Despite the evidence for primary care, however, resource allocation in most countries is still skewed toward hospitals and specialist care. [6,[11][12][13] The Korean health system has developed very rapidly in a short period, especially after the introduction of National Health Insurance in 1989-a universal coverage system compulsory for all citizens. The nation's efforts have been heavily focused on hospital-centered specialty care to meet growing demands of the population.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Despite the evidence for primary care, however, resource allocation in most countries is still skewed toward hospitals and specialist care. [6,[11][12][13] The Korean health system has developed very rapidly in a short period, especially after the introduction of National Health Insurance in 1989-a universal coverage system compulsory for all citizens. The nation's efforts have been heavily focused on hospital-centered specialty care to meet growing demands of the population.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified the top 10 international primary care research priorities; however, in contrast to the methodology used in the current study, this study grouped topics together under broad categories. 27 Although most of the top 10 international primary care research priorities featured within the top 21 priorities considered in this study, the differing methodologies might account for some differences between the two priority listings.…”
Section: Discussionmentioning
confidence: 97%
“…Frequently presenting conditions in general practice were also considered, [24][25][26] as were the recently determined top 10 international primary care research priorities. 27 The internal expert group then reviewed the list of priorities.…”
Section: Construction Of a Master List Of Prioritiesmentioning
confidence: 99%
“…The Delphi process is a formalised method for obtaining consensus, whereby participants respond to successive questionnaires that aim to identify common principles or proposals 9 10. It is used for multiple purposes, including determining common priorities for research 11–14. Responses are qualitative (free text comments) and quantitative (assigning ranks/scores).…”
Section: Methodsmentioning
confidence: 99%